(untitled) (International journal of artificial intelligence, 2025)
This article explores assessment criteria for evaluating independent learning competencies in educational contexts. As learners increasingly engage in self-directed study, especially with digital and hybrid learning environments, educators must develop reliable indicators to assess autonomy, motivation, goal-setting, time management, resource use, and self-reflection. This paper reviews existing frameworks and offers practical criteria that align with cognitive, metacognitive, and affective domains of learning. Drawing on current research and classroom practices, it discusses implications for curriculum designers, instructors, and policy-makers. The findings emphasize the importance of transparent, multi-dimensional, and formative approaches to measuring independent learning competencies effectively.